حماية التّعاقد الإلكتروني ومدى أهميته في حياتنا المعاصرة في ظلّ انتشار وباء كورونا - Adem Mohamed Cafcouf; Mohd Zaidi Bin Daud; Mohd Hafiz bin Jamaludin (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-PROCEEDING 3rd INTERNATIONAL CONFERENCE OF THE POSTGRADUATE STUDENTS AND ACADEMICS IN SYARIAH AND LAW 2020 (3rd INPAC 2020) "Syariah and Law Approach in Solving Contemporary Issues" Organized by: Faculty of Syariah and Law Date: 18 November 2020